Level of Interest of Tourists Visiting Jam Gadang Tourism Attraction Bukittinggi - Hibatullah, Naufal; Rahman, Fadlul; Hidayat, Taufik (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
In this research, the objectives to be achieved are certainly in line with the problems discussed. Based on the problems described previously, the aim of this research is to analyze the interests of tourists visiting the Bukittinggi Jam Gadang tourist area, to analyze the performance of the management of the Bukittinggi Gadang Jam tourist area, to design a development strategy based on tourist satisfaction with the performance of tourism products in the tourist area. Bukittinggi jam gadang This research is expected to be an input for managers in creating new innovations that can increase the satisfaction of tourists visiting the Bukittinggi gadang jam tourist area. This research uses a quantitative approach to examine the factors that influence tourist satisfaction in the Bukittinggi Jam Gadang tourist area. This aims to determine the right strategy to increase tourist visits. Indicators that influence the satisfaction of tourists visiting the Jam Gadang Bukittinggi tourist area, ranked from the most significant, are attractiveness, variety of activities, cleanliness, comfort, security, ease of registration, convenience of public toilets, ease of access to the location, friendliness of employees, attitude of souvenir sellers. , price of admission. The performance of tourism products does not exceed the level of interest of visiting tourists. It was concluded that there was dissatisfaction with tourists. The strategy for developing tourism products in the Bukittinggi Jam Gadang tourist area is in accordance with the focus quadrants that have been determined in the discussion.